Professional Roles, Challenges, and Adaptive Resilience of Neurosurgical Teams in Delivering Service Excellence Within Resource-Limited Hospital Settings - Sirait, Anton MJ; Pamungkas, Rian Adi; Kusumapradja, Rokiah (Alta Dharma Publisher, 2025)
Introduction: Neurosurgical services in Class B hospitals present a high level of complexity due to limitations in technology, facilities, and human resources. This study aims to explore the subjective experiences of neurosurgical medical teams, comprising neurosurgeons, nurses, anesthetists, medical equipment technicians, and operating room managers, in interpreting their roles, confronting challenges, and developing adaptive strategies to support excellent healthcare services at a Class B hospital. Methods: Employing a qualitative phenomenological approach, data were collected through in-depth interviews and analyzed thematically following Colaizzi’s method. Results: The findings indicate that service excellence in neurosurgical care within a resource-limited hospital is maintained through the dynamic interaction between professional meaning-making, persistent multidimensional challenges, and adaptive resilience strategies. While individual and team-level adaptations effectively sustain daily performance, limited systemic support poses challenges to long-term sustainability. Conclusion: Overall, the study highlights that the success of excellent neurosurgical services in Class B hospitals depends more on personal resilience and team cohesion than on systemic support alone. Recommendation: It recommends systemic improvements in management, human resource policies, integrated communication systems, and sustainable psychosocial support to ensure the continuity of high-quality services amid structural limitations